Problems at Crumpton - Staley, Alan; Mackenzie, Niall (Proceedings of the International Conference on Networked Learning, 2000)
The 'Problems at Crumpton' project is just one of a number of projects included in the four year Computer Supported Experiential Learning (CSEL) project at the University of Central England. Crumpton is an online spoof university that is having problems because of poorly designed curricula. Academic staff can access the Crumpton website, discover the problems by examining fictitious course documentation and watching a series of short video clips that vividly represent practice at Crumpton University. These clips, which are situated in real world contexts, include a conflict between external examiners, a mutiny in the staff common room, an employer enquiring about the students' skills, inappropriate teaching methods, and a student rebellion. The intention of this problem-based curriculum is to provide the motivational context in a fairly humorous way. Once academic staff have analysed the problems there is a structured study programme to follow, and then a conference in which to collaboratively discuss the issues and suggest tentative solutions. The context for 'Problems at Crumpton' is to provide innovative staff development for University tutors.